Pandangan Tokoh Masyarakat dan Pedagang Wonocolo terhadap Penggunaan Uang Rusak atau Cacat pada Transaksi Jual Beli dalam Perspektif UU No. 7 Tahun 2011 - Zahra, Zahra; Anggraini, Enggita Dwi; Sumarno , Dicky; Za'far, Yanuar Aditya; Hikmah, Zahro'atul Qolbu Nur; Rohman, Moh. Faizur (Maliyah : Jurnal Hukum Bisnis Islam, 2023)
Buying and selling transactions using damaged/defective money is a topic of concern in the Islamic view. Because of this, this research was made to discuss the use of damaged/defective money in buying and selling transactions from the point of view of community leaders and traders in Wonocolo District which will then be analyzed by Law Number 7 of 2011. This research was conducted through a qualitative approach using interviews and participatory observation as method of collecting data. The results of the study show that there are differences of opinion between community leaders and traders regarding the use of damaged/defective money in buying and selling transactions. Some community leaders and traders are of the opinion that the use of damaged/defective money in buying and selling transactions is not in accordance with the legal perspective stipulated in Law Number 7 of 2011. They are of the opinion that the money used in transactions must meet the criteria of validity, not be defective, and have stable exchange rate. They also stated that the use of damaged/defective money could violate the principles of fairness and reduce trust in buying and selling transactions. However, different views also emerge, especially among traders.